2021
DOI: 10.3390/app11167634
|View full text |Cite
|
Sign up to set email alerts
|

Ultimate Compressive Strains and Reserves of Bearing Capacity of Short RC Columns with Basalt Fiber

Abstract: Increasing the bearing capacity of reinforced concrete structures, reducing material consumption, and ensuring quality are critical in modern construction. The article presents an experimental study of the ultimate compressive strains of short fiber basalt reinforced concrete columns and provides recommendations for increasing the bearing capacity using steel reinforcement bars with greater strength. The columns were tested in an upright position using a hydraulic press. Strains were measured with dial indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…Similar findings provided by Dong et al [13] pointed to substantial environmental impact of applied epoxy resin and lubricating agents. The obtained values are in agreement with the presumptions of various authors, who attributed reduced environmental impact to BF production, in comparison to steel or glass fibers [22,34]. As observed in the work of Akbar et al [16], almost all currently used types of fiber reinforcement are linked to a similar impact on aquatic organisms by acidification.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Similar findings provided by Dong et al [13] pointed to substantial environmental impact of applied epoxy resin and lubricating agents. The obtained values are in agreement with the presumptions of various authors, who attributed reduced environmental impact to BF production, in comparison to steel or glass fibers [22,34]. As observed in the work of Akbar et al [16], almost all currently used types of fiber reinforcement are linked to a similar impact on aquatic organisms by acidification.…”
Section: Resultssupporting
confidence: 90%
“…Unlike carbon or steel fibers, reliable datasets describing the environmental load associated with basalt fiber application are lacking in the available literature, and only a few pioneer works can be identified. Therefore, an understanding of the environmental impact associated with basalt fiber reinforcement needs to be provided in order to allow advanced comparison and responsible selection of individual concrete mixture constituents [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In another experiment executed by Shilov et al [2], the differences between basalt fiber reinforced concrete and common concrete under compression are also analyzed. The results of testing ten simples revealed that 10% increase in coarse basalt fiber content increased the maximum compressibility of different kinds of concrete by around 20%.…”
Section: Figurementioning
confidence: 99%